TERAPI OUTBOUND UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA SMA NEGERI 4 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This research aims to find out the social skills of students before and after outbound therapy, to find out the differences in students' social skills before and after being given outbound therapy, to find out the effect of outbound therapy on improving students' social skills. This research is quantitative research with experimental methods, the design of the research used is Pre-Experimental with the approach of one group pre-test and post test subjects in this study are 20 students who have low social skills. The results showed that there was an increase in social skills before and after being given outbound therapy, before being given therapy in the very low category of 20% and in the low category by 55% and in the moderate category by 25%, after being given outbound therapy experienced an increase in the moderate category by 5%, the high category by 85% and in the very high category by 10%. Wilcoxon test results show Asymp. Sig. (2-tailed) or probability value of (0.000) < α (0.05) meaning Ha is accepted and Ho is rejected. This suggests there has been a significant improvement in social skills by being given outbound therapy. In addition, based on spearman rank tests it is known that there is an influence of outbound therapy to improve the social skills of students 44.7% while 57.3% is influenced by factors that come from within the student as well as from the student environment.Key Words: Outbound Therapy, Social Skills